Registration of HA‐R14, HA‐R15, HA‐R16, and HA‐R17 oilseed sunflower germplasm with broad resistance to rust and downy mildew. Issue 1 (13th October 2021) - Qi, Lili; Ma, Guojia; Seiler, Gerald
Abstract: Rust and downy mildew (DM) are two of the most important sunflower diseases in the world. The development of sunflower hybrids with enhanced levels of genetic resistance to both diseases is a goal for sunflower breeding. Four oilseed sunflower ( Helianthus annuus L.) germplasm lines, HA‐R14 (Reg. no. GP‐371, PI 698193), HA‐R15 (Reg. no. GP‐372, PI 698194), HA‐R16 (Reg. no. GP‐373, PI 698195), and HA‐R17 (Reg. no. GP‐374, PI 698196) are multiple rust‐ and DM‐resistant lines that were developed and released by the USDA‐ARS Sunflower and Plant Biology Research Unit in collaboration with the North Dakota Agricultural Experiment Station in January 2020. Three lines, HA‐R14 ( R4 R4 / R12 R12 / PlArg PlArg ), HA‐R15 ( R5 R5 / R12 R12 / PlArg PlArg ), and HA‐R16 ( R13b R13b / R12 R12 / PlArg PlArg ), stack two different rust genes with a common DM gene PlArg, and HA‐R17 ( R13b R13b / R15 R15 ) possesses two rust genes, R13b and R15 . These germplasm lines will provide a broad spectrum of useful sources of resistance to all known races of rust and DM. Core Ideas: Four oilseed sunflower germplasm lines with dual disease resistance were developed by MAS. HA‐R14, HA‐R15, and HA‐R16 combine two different rust R genes and a downy mildew R gene. All germplasm exhibited resistance to all known races of rust and downy mildew. HA‐R17 combined two different rust R genes resistant to all known races of rust.